Analisis Kontekstual pada Variasi Jamak dari Satu Mufrad dalam Al-Qur’an al-Karim / The Contextual Analysis on the Plural Variations of One Singular in the Al-Qur'an al-Karim - Khairuddin, Khairuddin; Zaenal Abidin,; Khaerun Nisa Nuur, (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The plural variation for one word called the plural taraduf is one of the many unique features of the Arabic language. Variations are interesting because the difference in plurality gives different meanings. This study aims to examine the taraduf of the plural form in the Al-Qur'an al-Karim in terms of contextual meaning. This is a kind of library research with a linguistic-semantic approach. The analytical technique used is a content analysis by digging up the mufradat of the Al-Qur'an al-Karim to obtain several plural forms and ensuring the existence of taraduf for the plural forms found. The results of this study indicate that in the Al-Qur'an al-Karim there are words that have two plurals. Uniquely, although the plurals are different, they still show the same meaning or taraduf, except for one plural variation of the same word, and two different plurals with different meanings (‘Adamu taraduf). Research on the plural taraduf is related to the texts of the Al-Qur'an, while there are still many sources of Islamic teachings which are also in Arabic, so the results of this study can be an alternative reference in conducting research. similar research.